Production of bioethanol using rotten fruit / Harith Aimiros ...[et al.] - Aimiros, Harith; Ghazali, Nur Athirah; Abd Ghani, Ainur Anisah; Sukor, Mohd Zaki
Bioethanol, which one of the renewable biomass fuel is used as petrol substitution is mostly used in the world since it reduces the usage of crude oil and reduces the environmental pollution at the same time. This study is conducted to identify the most suitable rotten fruits that can be used in producing bioethanol. The rotten fruits are mixed with yeast, S. cerevisiae at two different temperatures, 30 °C and 35•c, which are then fermented for 8 days. From this study, mixed fruits have the highest percentage of bioethanol at the temperature 30 °C with the reading of7.5899 % (v/v).